Productivity of indigenous sheep and goats in the Ada district of the Ethiopian highlands - Mukasa-Mugerwa, E.; Bekele, E.; Tessema, T. (1986)
The productive performance of indigenous sheep and goats of Ethiopia were evaluated over a period of 2 years (October 1979 to March 1981). Data on age at first parturition, litter size, lambing and kidding intervals, annual reproductive rates, mortality rates and growth rates included.